Incarcerated mothers’ experience of adversity heard using participatory mixed-method research - O’Malley, Sinead (Probation journal, 2023)
This article is based on mixed-method participatory research with incarcerated mothers in Ireland. It draws on this research which aimed to profile imprisoned mothers, hear their experiences of motherhood and mothering and examine their available supports. An overview of relevant literature on motherhood, incarceration, trauma and addiction in the context of incarceration is presented, followed by a detailed outline and discussion of the participatory methods used. Participants were involved in the design and implementation of the research, but not the data analysis and reporting. Prominent themes highlighted in the lives of participants include trauma, addiction and mother–child separation. Rich accounts of child and adult trauma, associated addiction and criminality and voluntary and enforced separations from their children are described and discussed. The article concludes with a reflection on the key issues that arose for participants and considers how these might be responded to in the future.